A Dynamic Multidomain Green‐Ampt Infiltration Model - Stewart, Ryan D. (Water resources research, 2018)
Shrink‐swell soils possess dynamic hydraulic properties, which may limit the applicability of traditional models for simulating infiltration and overland flow. This study incorporates Green‐Ampt infiltration concepts into a multidomain porosity framework to account for variations in pore size distributions and saturated hydraulic conductivities caused by soil shrinkage and swelling. The model requires three input variables (initial water content, rainfall rate, and time) and up to 15 parameters to simulate infiltration and overland flow, though most of the parameters are universal constants or can be estimated from auxiliary measurements. In comparison, the classic Green‐Ampt model, which assumes constant hydraulic properties and a single domain, requires the same three inputs and up to seven parameters to use. Performance of the proposed multidomain model was verified with two data sets. The first came from a study in Mexico where time to ponding and soil matrix infiltration were quantified under simulated rainfall, and the second came from a study in Chile where overland flow was measured during irrigation experiments on runoff plots. By tuning two (Chile) or three (Mexico) parameters, the multidomain model provided accurate estimations of infiltration/runoff partitioning at multiple scales. Compared to the classic single‐domain model, the multidomain model had lower root‐mean‐square deviations (reducing simulated infiltration errors by 2–3 times) and Akaike Information Criterion (AIC) scores (ΔAIC ~100), thus providing better simulations of infiltration, ponding, and runoff. These results demonstrate that modeling hydrological processes in shrink‐swell soils necessitates separating soil properties mediated by the matrix from those associated with interblock shrinkage cracks. Plain Language Summary Many soils develop cracks as they dry. During rainstorms and irrigation events, these cracks permit water to move rapidly, but we do not currently possess appropriate tools to simulate water movement in such conditions. This study proposes a mathematical model that calculates water infiltration into such soils by explicitly accounting for properties of cracks versus those of the surrounding soil. The model was verified using field observations from two locations, which demonstrated that the model can accurately simulate water infiltration, ponding on the soil surface, and surface runoff in soils containing cracks. Key Points This model incorporates Green‐Ampt infiltration concepts into a dynamic multidomain porosity framework Model was verified on two soils, improving estimates of infiltration and ponding compared to the classic Green‐Ampt model Most model parameters can be constrained using universal constants or auxiliary measurements